Time and spatial contrast analysis of noise levels in the commercial markets in city of Hama_Syria: Market noise in the city of Hama_Syria (Journal of Hama University, 2026)
Abstract:Noise emitted from commercial markets is one of the most prominent problems facing the city of Hama. It has become one of the pollutants affecting the quality of life there, and its prevalence is a concern for residents. This is due to the city's lack of environmental awareness and the absence of environmental legislation, such as standards that residents must adhere to or legal deterrents that would mitigate the severity of this problem and its effects on human health and activities. The research concluded that Hama's markets are exposed to several noise sources, including transportation and other human activities. High noise levels exceeding (94) decibels were recorded. (6) Sites were identified for periodic measurements in Hama, from the beginning to the end of 2022. A Taiwanese-made Digital Sound Level Meter 824 was used to measure noise intensity, and the Geographic Information Systems (GIS) program (Arc Map 10.8) was used to draw the maps necessary for the research.The monitoring sites have been identified as noise-polluted, exceeding the World Health Organization (WHO) and Syrian standards (SASMO) at high levels, as demonstrated by a field study. These high levels may increase in value in the coming years unless the necessary measures are taken to reduce and combat them, through public education and the implementation of controls or laws that deter violators, to limit and control this problem.
Keywords: Keywords: Pollution - Noise - Hama - Decibels.